2015
DOI: 10.7603/s40681-015-0015-8
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of (-)-epigallocatechin-3-gallate against acetaminophen-induced liver injury in rats)

Abstract: (-)-Epigallocatechin-3-gallate (EGCG) is the most abundant catechin with various biological activities found in tea. In this study, the effects of EGCG on the metabolism and toxicity of acetaminophen in rat liver were investigated. Male Sprague-Dawley rats were fed a controlled diet without or with EGCG (0.54 %, w/w) for 1 week and were then intraperitoneally injected with acetaminophen (1 g/kg body weight) and killed after 12 h. Concentrations of acetaminophen and its conjugates in plasma and liver were then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 29 publications
2
23
0
2
Order By: Relevance
“…et al, 2015 ; Wu I.C. et al, 2015 ; Yao et al, 2015 ; Yin, 2015 ; Lai et al, 2017b ; Liao et al, 2017b ). A population-based retrospective cohort study was conducted using the database from the Taiwan National Health Insurance Program.…”
Section: Methodsmentioning
confidence: 99%
“…et al, 2015 ; Wu I.C. et al, 2015 ; Yao et al, 2015 ; Yin, 2015 ; Lai et al, 2017b ; Liao et al, 2017b ). A population-based retrospective cohort study was conducted using the database from the Taiwan National Health Insurance Program.…”
Section: Methodsmentioning
confidence: 99%
“…Treatment with antioxidative agents has been widely considered to treat oxidative stress induced damages (Amara et al, ; Chen et al, ; Guzman‐Guillen et al, ; Hsieh et al, ; Tsai et al, ; Yang et al, ; Yao et al, ; El‐Sayed el et al, ; Sahu et al, ). Coenzyme Q10 (Q10) is a powerful antioxidant used as a nutritional supplement for cancer patients undergoing chemotherapy and as treatment for heart failure, diabetes, breast cancer, and hypertension (Niklowitz et al, ; Madmani et al, ; Yeung et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Thoughtfully, the anti-oxidative effects of EGCG come into action through activation of anti-oxidation protective signaling, thus reducing injury [28,29]. Similarly, other studies have shown anti-oxidative and preventive effects of EGCG on different hepatic injury animal models [30,31].…”
Section: Discussionmentioning
confidence: 95%